THE UNLAWFUL PROOF OBTAINED THROUGH PERSONAL JOURNAL CARRIED OUT BY PRIVATE SECURITY IN STJ JURISPRUDENCE AND THE LEGAL EFFECTIVENESS OF FUNDAMENTAL RIGHTS IN RELATIONS BETWEEN PRIVATE (Reflection and Critique Law Magazine, 2022)
The discussion about the effectiveness of fundamental rights in private relations was highlighted in the news with the recent decision of the 5th Panel of the Superior Court of Justice (SCJ). The decision established a legal thesis that only the judicial authorities, police and their agents are the competent authorities to perform home or personal search. The unpublished decision in the Habeas Corpus case file 470.937-SP (2018/0250223-0) encourages analysis by the Science of Law. The purpose of this article is to propose an assessment of the effectiveness of fundamental rights among individuals from the res judicata case. Methodologically, the analyses of the doctrine and national legislation on the subject is adopted, applying the deductive logical method from a larger premise - constitutional and infraconstitutional legal norms - to a minor premise – the specific case judged by the SCJ, highlighting the direct effectiveness of fundamental rights in private relations.